Malaria prevention practices and associated environmental risk factors in a rural community in Wakiso district, Uganda - Musoke, David; Miiro, George; Ndejjo, Rawlance; Karani, George; Morris, Keith; Kasasa, Simon; Nakiyingi-Miiro, Jessica; Guwatudde, David; Musoke, Miph Boses (PLoS ONE, 2018)
Besides use of insecticide-treated mosquito nets (ITNs) and indoor residual spraying (IRS), other complimentary measures including suitable housing structures, and environmental management that reduce breeding of malaria vectors, can be implemented at households to prevent the disease. However, most studies on malaria prevention have focused mainly on ITNs and IRS. The aim of this study was therefore to assess malaria prevention practices beyond ITNs and IRS, and associated environmental risk factors including housing structure in rural Wakiso district, Uganda. Methods A clustered cross-sectional survey was conducted among 727 households in Wakiso district. Data were collected using an interviewer-administered questionnaire and observational checklist. The questionnaire assessed participants' household practices on malaria prevention, whereas the checklist recorded environmental risk factors for malaria transmission, and structural condition of houses. Poisson regression modeling was used to identify factors associated with use of mosquito nets by households. Results Of the 727 households, 471 (64.8%) owned at least one mosquito net. Use of mosquito nets by households was higher with increasing education level of participantsÐprimary (aPR = 1.27 [95% CI: 1.00±1.60]), secondary (ordinary level) (aPR = 1.47 [95% CI: 1.16±1.85]) and advanced level / tertiary (aPR = 1.55 [95% CI: 1.19±2.01]), and higher household income (aPR = 1.09 [95% CI: 1.00±1.20]). Additionally, participants who were not employed were less likely to have mosquito nets used in their households (aPR = 0.83 [95% CI: 0.70±0.98]). Houses that had undergone IRS in the previous 12 months were 42 (5.8%), while 220 (43.2%) households closed their windows before 6.00 pm. Environmental risk factors found at households included presence of vessels that could potentially hold water for mosquito breeding 414 (56.9%), and stagnant water in compounds 144 (19.8%). Several structural deficiencies on houses that could promote entry of mosquitoes were found such as lack of screening in ventilators 645 (94.7%), and external doors not fitting perfectly into walls hence potential for mosquito entry 305 (42.0%). Conclusion There is need to increase coverage and utilisation of ITNs and IRS for malaria prevention in Wakiso district, Uganda. In addition, other malaria prevention strategies such as environmental management, and improving structural condition of houses are required to strengthen existing malaria prevention approaches.
Keywords: Malaria prevention; Environmental risk factors; Rural community; Wakiso district; Uganda